Head rotation and the perception of eyelid height and contour - Daniel B Rootman; Elana Meer; Nicholas J Jackson; Stefania B Diniz; John M Nesemann (BMJ Open Ophthalmology)
Purpose Effective visual perceptual processing is one of the many components of surgical competence. Human face identification is most efficient when viewed upright. However, it is not yet clear how this perception sensitivity impacts eyelid symmetry. This study investigates surgeons’ and laypeople’s accuracy and efficiency in perceiving eyelid asymmetry from different spatial perspectives.Methods A prospective psychometric experiment was conducted where oculoplastic surgeons were recruited from the American Society of Ophthalmic Plastic and Reconstructive Surgery and the Brazilian Oculoplastic Surgery Society, and control participants were recruited via crowdsourcing (Amazon’s Mechanical Turk). Standard illustrations of the human face with varying degrees of eyelid abnormality, laterality, gender and rotation were presented to participants who were asked to judge whether the eyelids were symmetric or asymmetric.Results The survey was completed by 75 oculoplastic surgeons (49.33% male; mean age of 46.9±10.7) and 192 lay individuals (54.6% male; mean age 34.6±11.3 years). Among oculoplastic surgeons, deviation from upright was significantly associated with increased reaction time and decreased proportion correct (OR per 45° for peak 0.68, 95% CI 0.60 to 0.77, p<0.001; OR per 45° for ptosis 0.52, 95% CI 0.32 to 0.87, p=0.012; OR per 180° for aggregate responses 0.56, 95% CI 0.51 to 0.61, p<0.001). Oculoplastic surgeons demonstrated increasing accuracy and decreasing reaction time with additional trials for both peak and ptosis.Conclusion Oculoplastic surgeons perceive eyelid asymmetries more accurately and can better compensate for inverted sensory information. However, accuracy increases and reaction time decreases with additional trials, suggesting trainability and potential for improvement in inversion disability.